2015
DOI: 10.1038/srep16557
|View full text |Cite|
|
Sign up to set email alerts
|

Modeling crowdsourcing as collective problem solving

Abstract: Crowdsourcing is a process of accumulating the ideas, thoughts or information from many independent participants, with aim to find the best solution for a given challenge. Modern information technologies allow for massive number of subjects to be involved in a more or less spontaneous way. Still, the full potentials of crowdsourcing are yet to be reached. We introduce a modeling framework through which we study the effectiveness of crowdsourcing in relation to the level of collectivism in facing the problem. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 46 publications
1
21
0
1
Order By: Relevance
“…Almost 70% of Gnutella users share no files (Adar and Huberman 2000). The decrease in cooperative behaviour with the increase of group size, has found further confirmation in the simulations conducted by Guazzini and colleagues (Guazzini, Vilone, Donati, Nardi, and Levnajić 2015). When the tasks are not particularly demanding, the authors have observed that very large groups tended to have a minor fitness (i.e., score) compared to smaller groups.…”
Section: Introductionmentioning
confidence: 65%
“…Almost 70% of Gnutella users share no files (Adar and Huberman 2000). The decrease in cooperative behaviour with the increase of group size, has found further confirmation in the simulations conducted by Guazzini and colleagues (Guazzini, Vilone, Donati, Nardi, and Levnajić 2015). When the tasks are not particularly demanding, the authors have observed that very large groups tended to have a minor fitness (i.e., score) compared to smaller groups.…”
Section: Introductionmentioning
confidence: 65%
“…Generally speaking, there have been many attempts to exploit the properties of human information exchange in order to improve collective decision-making [1][2][3]. By means of social and cognitive-inspired simulations based on the sociophysics approach, in this paper, we employ a numerical simulation framework for crowdsourcing [4] in order to investigate the role of the cost of cooperation and its interaction with other variables (group size, difficulty of the task, the presence of selfish individuals, etc.). We highlight the importance of the cost of cooperation and determine the conditions where higher costs do not hinder the overall performance.…”
Section: Introductionmentioning
confidence: 99%
“…In case of a large conflict between groups, on the contrary, the group with more cooperators is subject to win [17]. Thus frequent occurrence of group-level conflicts would explain the survival of cooperation.…”
Section: Introductionmentioning
confidence: 99%